First approaches for the transplantation of hepatocytes from Wistar rat preneoplastic livers into healthy recipients - Vera, Marina Cecilia (2019)
Background: the shortage of donors of hepatocyte transplantation therapy led to the use of so-called marginal donors. Some donors may have a hepatic illnesses that is associated with hepatic preneoplasia with foci of altered hepatocytes (FAH). Aims: to determine whether recipients developed FAH upon transplantation with hepatocytes from a preneoplastic liver and whether FAH progresses to a preneoplastic hepatocyte- derived tumor (PHDT), up to 60 days after transplantation. Material and methods: male Wistar adult rats were used as donors and recipients. Donors underwent a 2-phase model of liver preneoplasia for hepatocyte isolation. Recipients underwent a partial two thirds hepatectomy and received 150,000 hepatocytes. Recipients were euthanized seven and 60 days after transplantation. The number of FAH per liver area, percentage of liver occupied by FAH, the hepatic enzymatic profile, the percentage of prothrombin time (PT), the proliferative index (PI) and liver morphology were analyzed. Results: recipients developed few and very isolated FAH. No statistical differences were found between hepatic enzyme activities and PT. There were no differences between the groups with regard to the number of FAH per liver area and percentage of liver occupied by FAH after 60 days. The PI decreased on day 60 compared to day seven. No morphological alterations were found. Conclusions: recipients developed few FAH that did not increase in number or size, nor did they progress to PHDT and had normal plasma biochemical features and liver morphology up to 60 days post-transplant. Additional studies are needed to determine whether FAH development constitutes a risk for recipients while waiting for whole organ transplant.